EXPLORATION GEOMETRY TRANSFORMATION CONCEPT FROM SAMARINDA SARONG - Nur Fathaillah Pajrin; Haeruddin Haeruddin; Sugeng Sugeng (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Samarinda sarong is a masterpiece or special craft that lived in Samarinda city and one of the most icon from this city. This culture should be able to give attention to the people of Samarinda, because through education based on local wisdom it is able to grow the love of students to preserve the culture in which they live. The purpose of this study is to find out geometry transformation concept that found from Samarinda sarong design in Tenun village. The research method used is a qualitative research method with an ethnographic approach. The research was conducted at Cahaya Samarinda production site in RT.07 Weaving Village with the research subject being the samarinda sarong and the object of research is the geometry transformation concept that is in the sarong motif made. Research data were collected using documentation techniques. Data analysis was carried out by reducing, presenting, making conclusions, and then presented in detail by linking supporting theories. Form explore result have found geometry transformation concepts such as translation, reflection, rotation, dilatation and some compotitions that was happened.